Protein fraction and digestibility of marandu, xaraes and campo grande grasses in monocropping and intercropping systems under different sowing methods - doi: 10.4025/actascianimsci.v35i1.15134 - Juliane Ferreira Morais Moreira; Kátia Aparecida de Pinho Costa; Eduardo da Costa Severiano; Patrícia Soares Epifânio; Welma Santos Crunivel; Kátia Cylene Guimarães (Acta Scientiarum. Animal Sciences, 2012)
A study was carried out to evaluate the protein fraction and in vitro dry matter digestibility of marandu, xaraes grasses and campo grande in monocropping and intercropping systems under different planting methods, for a period of two years. The experimental design was a complete randomized block with four replications. The treatments consisted of the following crop systems: campo grande in monocropping; xaraés grass in monocropping; marandu grass in monocropping; xaraés intercropped with campo grande in rows; xaraés intercropped with campo grande, broadcast; marandu grass intercropped with campo grande in rows; and marandu intercropped with campo grand, broadcast. The evaluations were conducted for two years, consisting of seasonal evaluations (autumn, winter, spring and summer) in the same plots, with repeated measurements over time. The results showed that xaraes and marandu grasses were similar between crop systems, indicating that both can be intercropped with campo grande. The intercropping of campo grande with Brachiaria brizantha cultivars improved the protein fraction and digestibility. The row method of planting provided better protein fractions and in vitro dry matter digestibility.